Pelatihan Metode Tahsin dalam Upaya Meningkatkan Kemampuan Membaca Al-Qur`an Di TPQ Darussalam Desa Prajegan sukorejo ponorogo - Siti Nur Mutmainnah; Asfahani Asfahani; Moh Masduki (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article examines the implementation of Tahsin Al-Qur’an learning at TPQ Dasussalam. The aim of this study is to evaluate the Qur'an reading ability of the students and to improve their reading skills in accordance with Islamic principles. The results of the Tahsin learning show a satisfactory improvement according to standards, from planning and implementation to evaluation. This research is field-based with a qualitative approach. Data collection techniques include observation, interviews, and documentation. The Tahsin materials use the Asyafi'i book, and teachers employ the talaqqi method to enhance students' reading quality. The supporting factors for the success of the learning process are cooperation with the students' guardians, while the inhibiting factors are limited time and the teachers' difficulty in maintaining the students' enthusiasm and concentration during the learning sessions.